Taharqa, not Ushanahuru: Reconsidering the identity of the African individual on the victory stele of Esarhaddon - Karlsson, Mattias (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
The Victory Stele of Esarhaddon (VA 2708) conveys a scene in which the Assyrian king Esarhaddon (680-669 BCE) stands holding two foreign potentates by lead ropes (ṣerretu), with the ropes ending in rings fastened to the lips of the potentates. A text which commemorates the conquest of Egypt by Assyria in 671 BCE accompanies the scene.